THE IMPACT OF ONLINE MEDIA COVERAGE OF SEXUAL VIOLENCE AGAINST WOMEN AND CHILDREN TOWARDS WONOGIRI SOCIETY - Asih, Situ (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Sexual violence against women and children in Wonogiri Regency, especially in 2023, will experience a very high increase in cases. The occurrence of sexual violence made the mass media busy reporting it, especially on online media. This article aims to describe the impact of reporting on sexual violence against women and children in Wonogiri Regency in online media. The method used to answer the research questions in this article is descriptive qualitative where researchers obtain data through direct observations and in-depth interviews with informants. The results of the research show that reporting in online media regarding sexual violence against women and children in Wonogiri Regency has several impacts. Among the positive impacts are: 1) increasing public knowledge regarding various sexual violence against women and children in Wonogiri Regency, 2) Due to increasing public knowledge, a sense of concern for the surrounding environment appears, people are more concerned and no longer indifferent to the incidents that occur around, 3) Furthermore, a sense of mutual protection among members of the community grows, this is because the community does not want similar incidents to occur in the environment where they live. However, reporting via online media also turns out to have a negative impact among society, namely: 1) Excessive fear, excessive fear because people get information from online media regarding sexual violence against women and children. Especially in families with school-age children, it is normal for fear to arise. Apart from that, the negative impact is 2) becoming restless and always suspicious.